LPS promotes the production of ROS in neutrophils to regulate their killing activity against Mycobacterium tuberculosis - Lina Jiang; Zhenxing Su; Yangxiao Zhang; Hongsheng Liu; Hongtao Wang (Scientific Reports)
Abstract Tuberculosis (TB) is now the leading cause of death globally from a single infectious disease. So far, the exact mechanism of anti-tuberculosis immunity has not been fully elucidated, and the immune role of neutrophils in anti-tuberculosis infection is controversial. We investigated the killing function of neutrophils against Mycobacterium tuberculosis (M.tb) and the effect of neutrophils activated by lipopolysaccharide (LPS) on the production of reactive oxygen species (ROS), to evaluate the mechanism by which neutrophils eradicate M.tb mediated infection and find theoretical basis for clinical treatment of tuberculosis. The killing rate of neutrophils to FDA (Fluorescein diacetate)-labeled M.tb was detected by flow cytometry, and the killing rate of neutrophils to M.tb was observed by fluorescence microscopy. The activation rate and ROS production of neutrophils were observed at different time points after M.tb infection. Flow cytometry was utilized to detect the effect of LPS on the ROS production during neutrophil mediated killing of M.tb. Toll-like receptor 4 (TLR4) monoclonal antibody or NADPH oxidase inhibitor was utilized to detect the LPS activated neutrophil mediated production of ROS during M.tb killing. The killing function of neutrophils against M.tb increased with time. The activation rate and ROS production of neutrophils increased with time after M.tb infection. The activation rate and ROS production of neutrophils increased with the increase of LPS concentration. The activation rate and ROS production of PMN were reduced by TLR4 monoclonal antibody or NADPH oxidase inhibitor.LPS-TLR4 pathway is involved in neutrophils induced ROS mediated killing of M.tb. LPS promotes neutrophils mediated killing of M.tb, through ROS mediated production of NADPH oxidase which provides a theoretical basis for testing the role of neutrophils in clearance of M.tb in humans, and reducing the M.tb pathogenesis.